Accessibility Investigation of Large Magnetic Entropy Change in CoMn1-xFexGe - Yüce, S.; Bruno, N.M.; Emre, B.; Karaman, I. (American Institute of Physics Inc. subs@aip.org, 2016)
The influence of Fe doping for Mn in CoMn1-xFexGe alloys on their structural and magnetic phase transitions was investigated. CoMn1-xFexGe alloys display a first-order magneto-structural transition from a high temperature paramagnetic hexagonal Ni2In-type crystal structure to a low temperature ferromagnetic orthorhombic TiNiSi-type structure. An entropy change of ΔSM = -32.8 J/kg K was measured and adiabatic temperature change of -8.0 K was computed for the x = 0.085 alloy under a magnetic field of 7 T in the vicinity of the phase transition at 317 K. With increasing Fe content, transition temperatures and magnetic entropy changes decrease. In addition to investigating the effect of replacing Mn with Fe, the accessibility of the giant measured entropy change was quantified by means of the minimum magnetic field required to start and to complete the magneto-structural phase transition. © 2016 AIP Publishing LLC.